Kinematics and kinetics of the bench-press and bench-pull exercises in a strength-trained sporting population - Pearson, S. N.; Cronin, J. B.; Hume, P. A.; Slyfield, D. (Sports Biomechanics, 2009)
Understanding how loading affects power production in resistance training is a key step in identifying the most optimal way of training muscular power - an essential trait in most sporting movements. Twelve elite male sailors with extensive strength-training experience participated in a comparison of kinematics and kinetics from the upper body musculature, with upper body push (bench press) and pull (bench pull) movements performed across loads of 10-100% of one repetition maximum (1RM). 1RM strength and force were shown to be greater in the bench press, while velocity and power outputs were greater for the bench pull across the range of loads. While power output was at a similar level for the two movements at a low load (10% 1RM), significantly greater power outputs were observed for the bench pull in comparison to the bench press with increased load. Power output (Pmax) was maximized at higher relative loads for both mean and peak power in the bench pull (78.6 ± 5.7% and 70.4 ± 5.4% of 1RM) compared to the bench press (53.3 ± 1.7% and 49.7 ± 4.4% of 1RM). Findings can most likely be attributed to differences in muscle architecture, which may have training implications for these muscles.